Impact of globalization and industrialization on ecological footprint: do institutional quality and renewable energy matter? - Li, Qiang; Zhang, Shuliang (Frontiers in Environmental Science, 2025)
Institutional quality (IQ) and renewable energy (RE) play crucial roles in reducing the ecological footprint (EFP), directly aligning with several United Nations Sustainable Development Goals (SDGs). IQ supports SDG-16 (Peace, Justice, and Strong Institutions) by designating effective governance, transparent policies, and legal frameworks that promote environmental sustainability. Renewable energy (RE) contributes enormously to SDG-7 (Affordable and Clean Energy) by providing sustainable, clean, and reliable energy sources that reduce dependence on fossil fuels. Adopting RE technologies also supports SDG-9 (Industry, Innovation, and Infrastructure) through investments in modern infrastructure and sustainable industrialization, fostering environmentally responsible economic growth. If institutions are strong, they ensure accountability and the implementation of regulations that facilitate the transition to RE, managing the SDG-13 (Climate Action) by actively combating climate change through policy and innovation. Therefore, the current study examines the impact of globalization and industrialization on ecological footprints (EFP) in six SAARC economies between 1996 and 2022, emphasizing the role of IQ and RE. We used the Fully Modified Ordinary Least Squares, Dynamic Ordinary Least Squares, Cross-sectional Autoregressive Distributed Lag (CS-ARDL), and panel causality approaches for the empirical study. The empirical findings demonstrate that globalization, industrialization, and GDP positively influence EFP, with coefficients of 0.82, 0.03, and 0.27. On the other hand, institutional quality, financial development, and renewable energy negatively affect EFP, with coefficients of −0.02, −0.70, and −0.30. Policymakers should establish and enforce stringent regulatory frameworks to ensure environmental accountability in industrial sectors, including mandatory compliance audits, transparent reporting mechanisms, and strict penalties for violations. Also, governments in SAARC countries should introduce targeted financial incentives, such as subsidies, tax exemptions, and concessional loans, to accelerate the adoption of RE solutions and promote sustainable economic growth and environmental sustainability. Moreover, SAARC countries should strengthen institutional transparency and anti-corruption frameworks to ensure fair and effective enforcement of environmental regulations.